METHODOLOGICAL AND DIDACTIC REQUIREMENTS FOR DEMONSTRATION EXPERIMENTS IN SECONDARY SCHOOL (Scientific journal of the Fergana State University, 2024)
The system of educational experiments in physics is interconnected, consisting of a collection of important experimental facts, experimental methods of physics, types of experiments performed and observed in the physics classroom, and organizational forms of teaching, education and development of students and the leading essence of the methodology of teaching physics.